2016
DOI: 10.1523/jneurosci.0257-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol and Agonism of G-protein-Coupled Estrogen Receptor Enhance Hippocampal Memory via Different Cell-Signaling Mechanisms

Abstract: The ability of 17␤-estradiol (E 2 ) to enhance hippocampal object recognition and spatial memory depends on rapid activation of extracellular signal-regulated kinase (ERK) in the dorsal hippocampus (DH). Although this activation can be mediated by the intracellular estrogen receptors ER␣ and ER␤, little is known about the role that the membrane estrogen receptor GPER plays in regulating ERK or E 2 -mediated memory formation. In this study, post-training DH infusion of the GPER agonist G-1 enhanced object recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(171 citation statements)
references
References 66 publications
(6 reference statements)
13
152
2
Order By: Relevance
“…In contrast, the GPER antagonist G-15 impairs spatial working memory in ovariectomized rats (Hammond et al, 2012). Consistent with these findings, post-training dorsal hippocampus or ICV infusion of G-1 enhances, whereas G-15 impairs, object recognition and object location memory consolidation (Kim et al, 2016). Unlike 17β-estradiol, however, G-1 does not increase ERK, PI3K, or Akt phosphorylation in the dorsal hippocampus, but rather increases activation of the c-Jun N-terminal Kinase (JNK) signaling pathway (Kim et al, 2016).…”
Section: Cell-signaling Pathways Involved In 17β-estradiol-inducedsupporting
confidence: 54%
“…In contrast, the GPER antagonist G-15 impairs spatial working memory in ovariectomized rats (Hammond et al, 2012). Consistent with these findings, post-training dorsal hippocampus or ICV infusion of G-1 enhances, whereas G-15 impairs, object recognition and object location memory consolidation (Kim et al, 2016). Unlike 17β-estradiol, however, G-1 does not increase ERK, PI3K, or Akt phosphorylation in the dorsal hippocampus, but rather increases activation of the c-Jun N-terminal Kinase (JNK) signaling pathway (Kim et al, 2016).…”
Section: Cell-signaling Pathways Involved In 17β-estradiol-inducedsupporting
confidence: 54%
“…A 24-hour delay was used to determine whether letrozole could block the memory-enhancing effects of E 2 on OP memory consolidation. At this time point, E 2 -infused, but not vehicle-infused, mice spend more time than chance with the moved object and E 2 -infused mice spend significantly more time with the moved object than vehicle-infused mice (Boulware et al, 2013; Kim, 2016). …”
Section: Methodsmentioning
confidence: 87%
“…A 48-hour delay was used to measure whether letrozole blocked the memory-enhancing effects of E 2 because vehicle-infused females show impaired OR memory consolidation, whereas E 2 -infused females show intact OR memory consolidation, at this time point (Fortress et al, 2013, Boulware et al, 2013). Moreover, E 2 -infused females spend significantly more time with the novel object than vehicle-infused females 48 hours after infusion (Kim, 2016). Because most mice inherently prefer novelty, those that remember the training objects spend more time than chance (15 sec) exploring the novel object during testing.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, estrogen effects via ERα and ERβ resulted in ERK1/2 activation whereas Kim et al, found that GPER activation led to phosphorylation of JNK. Infusion of a JNK inhibitor blocked G-1 enhanced object recognition whereas ERK inhibition did not (117). Taken together these experiments underscore the diversity of signaling mechanisms associated with hippocampal memory formation and further emphasize that a single ligand, in this case estrogen, can affect many pathways independently to regulate learning and memory.…”
Section: Introductionmentioning
confidence: 99%